Synthesis and Properties of La2Mo2O9 Nano-Powder Prepared via Sol-Gel Combustion Route - Tian, Changan; Zhao, Difang; Lu, Hongdian; Yin, Qiyi; Cheng, Jihai; Wu, Yun; Cao, Yan; Xie, Jingsong (Asian Journal of Chemistry, 2012)
In this study, ultrafine La2Mo2O9 powders have been successfully prepared by a novel sol-gel combustion route using a unique combination of citric acid. A range of analyzing techniques including XRD, TG-DSC and BET were employed to characterize the experimental powders. From the result of XRD patterns, we found that well-crystalline cubic structure La2Mo2O9 was obtained by calcining the precursor gel at 600 ºC for 2 h. The as-synthesized powders have an average crystallite size of 30 nm. It has also been found that the powders produced by sol-gel combustion method have fine sinterability, it can be sintered close to theoretical density at 950 ºC for 4 h.